Industri Mebel : Perkembangan Ekonomi Pengrajin Mebel Di Nagari Muara Panas Kabupaten Solok (1988-2021) - Sisri Wahyuni; Azmi Fitrisia (Jurusan Sejarah FIS UNP, 2023)
This study discusses the furniture industry: the economic development of furniture craftsmen in Nagari Muara Panas, Solok Regency (1988-2021) is motivated by the human need for furniture from year to year continues to increase along with the rate of population growth and households that need a house as a place to live. . The purpose of this study is to describe the background of the emergence of the furniture industry and to determine the influence of the furniture industry on the economy of furniture craftsmen in Kanagarian Muara Panas in 1988-2021. using the historical method. Qualitative research is a research procedure that produces descriptive data, through four steps as follows: (1) heuristics of collecting primary data through interviews aimed at owners and workers of the furniture industry, archives and observations conducted 4 times, while secondary sources are obtained from sources written in the form of a thesis, several journals and articles that the author found on the internet (literature), (2) source criticism (3 interpretations, (4) historiography, the discussion carried out can be seen that the economy of the economic community works as farmers and several small industries are included in it. the furniture industry. The furniture industry in Nagari Muara Panas is a wood processing industry that was pioneered and developed by the residents of Nagari Muara Panas themselves. In this area there are 7 furniture industries. Each furniture industry in Nagari Muara Panas has its own development, both from equipment, manufactured products and the number of employees. The existence of the furniture industry has an economic impact on both furniture owners and workers.Keywords: Development. Economy, Furniture Industry